Outcomes and risk factors associated with in-hospital mortality in patients undergoing coronary artery bypass grafting with low ejection fraction - Yang Zhao; Xu Yu; Xiaolong Ma; Liang Zhang; Zehui Wang; Zehui Wang; Zehui Wang (Frontiers in Cardiovascular Medicine)
ObjectiveTo investigate the short-term prognosis and risk factors associated with in-hospital mortality in patients undergoing coronary artery bypass grafting (CABG) with low ejection fraction.MethodsClinical data were collected from 765 patients who underwent CABG with an ejection fraction of less than 40% between 2019 and 2023 at Anhui Chest Hospital and Beijing Anzhen Hospital, Capital Medical University. The patients were categorized into a in-hospital mortality group (n = 38) and a in-hospital survival group (n = 727), based on whether they died within 30 days post-operation. Univariate and multivariate logistic regression analyses were employed to identify risk factors for in-hospital mortality. The relationship between these risk factors and the likelihood of in-hospital mortality was assessed using restricted cubic splines (RCS). Additionally, predictive values were evaluated by plotting receiver operating characteristic curves (ROC).ResultsIn-hospital mortality occurred in 38 out of the 765 patients, resulting in an incidence rate of 4.97%. Compared to the survival group, those in the mortality group exhibited significantly higher rates of exploratory thoracotomy, intra-aortic balloon pump usage, extracorporeal membrane oxygenation application, gastrointestinal bleeding incidents, and acute renal failure occurrences. Independent risk factors for in-hospital mortality included preoperative age, left ventricular ejection fraction (LVEF), fasting glucose levels (Glu), and glomerular filtration rate (eGFR). Conversely, standardized preoperative administration of oral nitrates and aspirin as well as intraoperative utilization of internal mammary arteries emerged as protective factors against in-hospital mortality. ROC analysis revealed predictive efficiencies for age at 68.5%, LVEF at 76.6%, Glu at 60.5%, while eGFR demonstrated a predictive efficiency of 78.1%.ConclusionThe incidence of in-hospital mortality in patients undergoing coronary artery bypass grafting with low ejection fraction is correlated with several factors, including advanced age, LVEF, Glu, eGFR, and the standardized preoperative administration of oral nitrates and aspirin. These findings serve as a guide for enhancing the in-hospital prognosis for this patient population in clinical practice.